PENGARUH PERIKLANAN TERHADAP PENJUALAN JASA MAKE UP WEDDING: PENGARUH PERIKLANAN TERHADAP PENJUALAN JASA MAKE UP WEDDING - Sunarta, Elfina Monica Sunarta (Journal of Beauty and Cosmetology (JBC), 2023)
Since ancient times, Indonesian women have known various ways to decorate themselves using traditional methods. but it has changed since the modernization of Indonesia, the meaning of beauty and cosmetics is linked to western countries. Although cosmetics that are in great demand by Indonesian women come from the West, local cosmetics can still be developed, such as Sariayu Martha Tilaar. Martha Tilaar is one of Indonesia's women entrepreneurs. Martha Tilaar founded a beauty company under the brand Sariayu, which uses ingredients from Indonesian nature. The more developed makeup service companies in Indonesia, the more competition that players in this industry must face. Therefore, many aspiring makeup artists (MUAs) are still confused about what to focus on or what to do in order for clients to see their makeup services and survive in the competition of the makeup business world. The purpose of this study is to determine the factors that influence the success of MUA Indonesia matches in managing the makeup service business. The purpose of makeup itself is to use cosmetic means and ingredients to make up or change the original shape with the aim of beautifying or covering imperfections so that the face looks perfect. Makeup actually has almost the same meaning as makeup. Makeup is the activity of changing the appearance of the original form actually with the help of cosmetic ingredients and tools. The term makeup is more often referred to changing the shape of the face, although actually the whole body can be decorated. Makeup is an important part of the show. Any event where someone performs on stage almost certainly requires makeup. In the Big Indonesian Dictionary (KBBI), make up consists of two words, namely make up and make up. Tata means rules, regulations, arrangements and ways of organization, while make-up is the decoration of something. According to Rusman Latief, Non-Drama Television Production Guidelines, makeup or makeup is the act of changing or complementing one's original appearance with cosmetic ingredients and tools.Keywords: business, Service Sales, wedding make up